2018
DOI: 10.1155/2018/6304701
|View full text |Cite
|
Sign up to set email alerts
|

Survival Mechanisms and Influence Factors of Circulating Tumor Cells

Abstract: Circulating tumor cells (CTCs) are cancer cells shed from either the primary tumor or its metastases that circulate in the peripheral blood. The CTCs are regarded as the source of tumor recurrence and metastasis and speculated as the indicators of residual tumors, thereby indicating a poor prognosis. Although CTCs play a vital role in tumor metastasis and recurrence, little is known about the underlying survival mechanisms in the blood circulation. The accumulating evidence has revealed that CTCs might survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 57 publications
0
63
0
Order By: Relevance
“…Single-cell sequencing data have shown increased expression of the EMT and stemness markers in CTCs (12). It has been postulated that activation of the EMT program facilitates CTC generation and enhances cancer cell survival in the circulation system (7,51). We found that Twist-induced EMT significantly enhanced MEC-platelet interaction, platelet-dependent extravasation, and MEC retention in the lung.…”
Section: Discussionmentioning
confidence: 64%
“…Single-cell sequencing data have shown increased expression of the EMT and stemness markers in CTCs (12). It has been postulated that activation of the EMT program facilitates CTC generation and enhances cancer cell survival in the circulation system (7,51). We found that Twist-induced EMT significantly enhanced MEC-platelet interaction, platelet-dependent extravasation, and MEC retention in the lung.…”
Section: Discussionmentioning
confidence: 64%
“…One reason for this may be that the epithelial cancer cells use stromal cells during invasion [87,88] (see more detail below). Solid tumors secrete a large number of highly heterogeneous circulating tumor cells (CTCs) into the bloodstream [89][90][91][92][93][94][95]. Still, only a small proportion of the CTCs (0.2% reported by Tripathi et al [96]) can survive and ultimately result in metastatic changes.…”
Section: Circulating Cancer Cells Form Clusters Through Tomo-and Hetementioning
confidence: 99%
“…Approximately only one cell per 10 6 -10 7 leukocytes remain [94]. The molecular mechanisms responsible for the formation and spread of clusters, and the pathways supporting their survival and metastatic potential remain mostly unknown [93].…”
Section: Circulating Cancer Cells Form Clusters Through Tomo-and Hetementioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that platelet interaction plays an important role in CTC survival. EMT-mediated platelet coating around the CTC surface provides a shield from natural killer (NK)-mediated tumor attack as well from the shear and dynamic stress in the bloodstream [46,47]. Furthermore, platelet depletion enhances the efficacy of NK cytolysis of CTCs [48].…”
Section: Ctcs In Circulationmentioning
confidence: 99%